Molecular detection of the reptile‐associated Borrelia group in Amblyomma dissimile, Mexico. Issue 2 (2nd September 2020) - Colunga‐Salas, P.; Sánchez‐Montes, S.; Ochoa‐Ochoa, L. M.; Grostieta, E.; Becker, I.
Abstract: Recently, the first record of Borrelia associated with reptiles in Mexico was published; however, no studies have been done to assess the role of Mexican ticks as potential vectors of this Borrelia group. Amblyomma dissimile is a hard tick mainly associated with amphibians and reptiles in this country. The aim of this study was to evaluate the presence of Borrelia in A. dissimile from Mexico. We collected 60 A. dissimile individuals attached to 16 Rhinella horribilis. DNA was extracted and all specimens were screened individually for Borrelia by amplification of a fragment of the 16S rDNA and an additional fragment of the flagellin gene. Five ticks were positive for Borrelia, DNA sequences corresponded to Borrelia sp. and group with sequences of the reptile‐associated Borrelia group. This is the first report of Borrelia in A. dissimile and the second report of the reptile‐associated Borrelia group in Mexico. This study also highlights the importance of this tick species as potential vector of this group. Abstract : Amblyomma dissimile as potential vector of the species of the reptile‐associated Borrelia group. Molecular confirmation of Borrelia in A. dissimile . Veracruz highlights as an interesting area for the study of the reptile‐associated Borrelia group.